2017
DOI: 10.1007/s10549-017-4598-5
|View full text |Cite|
|
Sign up to set email alerts
|

Breast-conserving surgery following neoadjuvant therapy-a systematic review on surgical outcomes

Abstract: PurposeNeoadjuvant chemotherapy (NACT) is increasingly used in breast cancer treatment. One of the main goals of NACT is to reduce the extent of local surgery of the breast and axilla. The aim of this study was to determine surgical outcomes for patients receiving breast-conserving therapy (BCT) after NACT, including margin status plus secondary surgeries, excision volumes, and cosmetic outcomes.MethodsA systematic review was performed in accordance with PRISMA principles. Pubmed, MEDLINE, Embase, and the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 57 publications
0
49
0
2
Order By: Relevance
“…The development of an accurate MRI-based measurement tool is of particular necessity for patients receiving NAC and BCS, a matter that needs to be urgently addressed. Our predictive equation may help to estimate accurately tumor size and to reduce the high rate (2–40%) of tumors on ink reported in patients undergoing BCS after NAC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of an accurate MRI-based measurement tool is of particular necessity for patients receiving NAC and BCS, a matter that needs to be urgently addressed. Our predictive equation may help to estimate accurately tumor size and to reduce the high rate (2–40%) of tumors on ink reported in patients undergoing BCS after NAC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 A recent systematic review of the available literature concluded that currently there is insufficient evidence to suggest that neoadjuvant chemotherapy improves surgical outcomes of BCS. 20 A retrospective study comparing the outcomes of OBS (45 patients) against standard BCS (214 patients) following neoadjuvant chemotherapy found higher rates of margin re-excision and completion mastectomy in the OBS group (31% versus 27% and 24% versus 18%, respectively). 21 In our work, despite of the rate of neoadjuvant chemotherapy being 1.5 times higher in the OBS group, this showed lower rates of margin re-excision and completion mastectomy than the WLE group.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of neoadjuvant chemotherapy on surgical margins is still controversial 20,21 . A recent systematic review of the available literature concluded that currently there is insufficient evidence to suggest that neoadjuvant chemotherapy improves surgical outcomes of BCS 20 . A retrospective study comparing the outcomes of OBS (45 patients) against standard BCS (214 patients) following neoadjuvant chemotherapy found higher rates of margin re‐excision and completion mastectomy in the OBS group (31% versus 27% and 24% versus 18%, respectively) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…NACT is associated with higher rates of local recurrence compared to ACT, which might be explained by the higher rates of breast conserving surgery among NACT-treated patients compared to patients undergoing primary breast surgery [48]. Several studies have shown difficulties in achieving tumor-free margins when performing primary breast conserving surgery, and a considerable number of reoperations are performed to obtain radical tumor excision [49]. Contributing factors might be difficulties associated with evaluating tumor size with imaging post-NACT [50,51].…”
Section: Mammographymentioning
confidence: 99%